Could capital gains smooth a current account rebalancing? - Michele Cavallo; Cedric Tille (Federal Reserve Bank of New York, 2006)
A narrowing of the U.S. current account deficit through exchange rate movements is likely to entail a substantial depreciation of the dollar, as stressed in research by Obstfeld and Rogoff. We assess how the adjustment is affected by the high degree of financial integration in the world economy. A growing body of research emphasizes the increasing leverage in international financial positions, with industrialized economies holding substantial and growing financial claims on each other. Exchange rate movements then lead to valuation effects as the currency composition of a country's assets and liabilities are not matched. In particular, a dollar depreciation generates valuation gains for the United States by boosting the dollar value of much of its foreign-currency-denominated assets. We consider an adjustment scenario in which the U.S. net external debt is held constant. The key finding is that as the current account moves into balance, the pace of adjustment is smooth. Intuitively, the valuation gains from the depreciation of the dollar allow the United States to finance ongoing, albeit shrinking, current account deficits. We find that the smooth pattern of adjustment is robust to alternative scenarios, although the ultimate movements in exchange rates will vary under different conditions.
Keywords: F31; F32; F41; 330; current account; exchange rates; global imbalances; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Auslandsvermögen; Vermögenszuwachs; Theorie; USA